The impact of off balance records on selected financial indicators of the cooperative bank assessment - Kurasz, Arkadiusz (Wpływ ewidencji pozabilansowej na wybrane wskaźniki oceny sytuacji finansowej banku spółdzielczego, 2017)
Financial crisis, regardless of the geographical coverage, subjective or sector, can be assessed from the perspective of two most important elements initiated: damage (eg. the collapse of Lehman Brothers) and changes (regulating the balance of power in the financial markets). The analysis of indicators used in assessing the financial situation of the cooperative bank on the basis of the selected documents shows that there are areas in need of renovation. The purpose of this article is to propose changes to the design rate of effectiveness of the cooperative bank, expressed as the ratio of operating costs to income from banking operations (KDB/WNB). The developed solution will provide information about the real revenues and expenses related to the core business of cooperative banks and will enable the same objective assessment of the effectiveness in this area of activity. The research methods adopted in the article are based on studies of literature, review of legislation, analysis of financial statements of the cooperative bank and conclusions
Nauki o Finansach = Financial Sciences, 2017, Nr 2 (31), s. 52-65
Keywords: financial crisis; off-balance records; assessment of the financial situation; a cooperative bank; indicator; kryzys finansowy; ewidencja pozabilansowa; ocena sytuacji finansowej; bank spółdzielczy; wskaźnik